Data Security in Public Cloud for Authorization - Gajeli, PB; Yalagi, PS (International Journal of Computer Sciences and Engineering, 2025)
Most of the security solutions use routers, firewalls, and intrusion detection systems implemented to tightly control, access to networks from outside authors. Cloud computing breaks these organizational bounds. When the data is present in the cloud, it resides outside the organizational bounds. Hence, a user loses control over their data. Another problem is, most of the time users are anxious about uploading private and confidential files for online backup due to concern that the service provider might use it inappropriately. So, providing security at the required level is a major concern. The existing solution is data-centric access control solution with an enriched role-based approach in which security is focused on protecting user data regardless the cloud service provider that holds it. In this, Novel rule-based and proxy re-encryption technique are used to protect the authorization model and increase the performance. The authorization model is rule-based file access control, i.e. permissions granted based on authority rules provided by the data owner. In this existing solution, the authorization model contains limited privileges which restrict modification and deletion. The proposed systems consist of two types of data viz. Normal data and Sensitive data. The user can upload the file and select the type of data. Protecting normal data by using proxy re-encryption technique and sensitive data by using rummage technique. The rummage technique which encrypts the original data into meaningful (readable) format, hence attacker gets confused to identify encrypted data. The authorization model is rule-based file access control that contains privileges like access, modify, delete, etc.